#### Answer

$f'(θ)= -2θsin(θ^2)$

#### Work Step by Step

Original Expression: $f(θ) = cos(θ^2) $
$u=θ^2$
$f(u)= cos(u)$
Apply the chain rule: $f'(u)u'$
$f'(u)= -sin(u)2θ$
$f'(θ)= -2θsin(θ^2)$

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$f'(θ)= -2θsin(θ^2)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.